Oligodeoxynucleotides inhibit retinal neovascularization in a murine model of proliferative retinopathy. - Robinson, G S (1996)
Diseases characterized by retinal neovascularization are among the principal causes of visual loss worldwide. The hypoxia-stimulated expression of vascular endothelial growth factor (VEGF) has been implicated in the proliferation of new blood vessels. We have investigated the use of antisense phosphorothioate oligodeoxynucleotides against murine VEGF to inhibit retinal neovascularization and VEGF synthesis in a murine model of proliferative retinopathy. Intravitreal injections of two different antisense phosphorothioate oligodeoxynucleotides prior to the onset of proliferative retinopathy reduced new blood vessel growth a mean of 25 and 31% compared with controls. This inhibition was dependent on the concentration of antisense phosphorothioate oligodeoxynucleotides and resulted in a 40-66% reduction in the level of VEGF protein, as determined by Western blot analysis. Control (sense, nonspecific) phosphorothioate oligodeoxynucleotides did not cause a significant reduction in retinal neovascularization or VEGF protein levels. These data further establish a fundamental role for VEGF expression in ischemia-induced proliferative retinopathies and a potential therapeutic use for antisense phosphorothioate oligodeoxynucleotides.